Factors affecting differences in measles-rubella bias immunization during the COVID-19 pandemic and before the COVID-19 pandemic in Kulon Progo District 2020 - Laksono, Bima Adi; Sitaresmi, Mei Neni; Arisanti, Risalia Reni (BKM Public Health and Community Medicine, 2022)
Purpose: This study examines the differences between MR bias immunization and the implementation of MR BIAS before (2019) and during (2020) the pandemic. Methods: This study was a qualitative study with a descriptive approach. Qualitative samples were selected using purposive sampling techniques. Twelve subjects were chosen as samples with occupations such as public health center officer, teacher, and parent. Results: Factors that influenced the implementation of the MR BIAS program before the pandemic (2019) and during the Pandemic (2020) were environmental factors, behavioral factors, and healthcare factors. Environmental factors that affect the implementation of vaccinations include online-based learning, delayed school immunization programs because of COVID-19 cases in schools, and the role of schools and teachers. Behavioral factors that affect the implementation of BIAS are the implementation of health protocols and the attitude of children and parents. Healthcare factors influencing vaccination implementation are immunization services constrained by human resources (HR) and personal protective equipment (PPE). Conclusion: There were differences in implementing monthly school immunization programs in 2019 before and in 2020 during the pandemic. Kulon Progo Regency maintained immunization coverage before and during the pandemic.